2015
DOI: 10.3389/fimmu.2015.00574
|View full text |Cite
|
Sign up to set email alerts
|

A SOCS1/3 Antagonist Peptide Protects Mice Against Lethal Infection with Influenza A Virus

Abstract: We have developed an antagonist to suppressor of cytokine signaling 1 (SOCS1), pJAK2(1001–1013), which corresponds to the activation loop of the Janus kinase JAK2, which is the binding site for the kinase inhibitory region (KIR) of SOCS1. Internalized pJAK2(1001–1013) inhibits SOCS1 and SOCS3. SOCS1 has been shown to be an influenza virus-induced virulence factor that enhances infection of cells. The antagonist was protective in cell culture and in influenza virus PR8 lethally infected C57BL/6 mice. The SOCS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Interestingly, SOCS1 promoter variants are associated with hepatitis B virus susceptibility [48], and SOCS3 expression and genetic polymorphism influence the pathogenesis and outcome of antiviral treatment in hepatitis C virus-infected patients [49]. Provided that the recently developed SOCS1/3 antagonist has a potent antiviral function against a broad group of viruses, such as herpes simplex virus-1, vaccinia virus, and influenza virus [50,51], it will be interesting to evaluate the effect of these antagonists against ZIKV infection. The findings of this study accompanied by prospective experimental results will better advance our comprehensive understanding of the pathogenesis of ZIKV-associated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SOCS1 promoter variants are associated with hepatitis B virus susceptibility [48], and SOCS3 expression and genetic polymorphism influence the pathogenesis and outcome of antiviral treatment in hepatitis C virus-infected patients [49]. Provided that the recently developed SOCS1/3 antagonist has a potent antiviral function against a broad group of viruses, such as herpes simplex virus-1, vaccinia virus, and influenza virus [50,51], it will be interesting to evaluate the effect of these antagonists against ZIKV infection. The findings of this study accompanied by prospective experimental results will better advance our comprehensive understanding of the pathogenesis of ZIKV-associated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The deficiency of SOCS1 protein causes a neonatal fatal inflammatory disease [ 39 ], while its overexpression in experimental autoimmune encephalitis (EAE)attenuates IFN-γ destructive effects [ 40 ]. Further, the over-expression of SOCS3 inhibits triple negative breast cancer (TNBC) growth and the formation of metastasis in mouse xenograft models, and its loss implies risk of relapses in TNBC patients [ 41 ].…”
Section: Peptides and Peptidomimetics As Modulators Of Inflammatiomentioning
confidence: 99%
“…In experimental allergic encephalomyelitis (EAE) mice model, KIR peptide was also able to contrast the action of CD4+ Th1 and Th17 cells on the blood-brain barrier (BBB). Indeed, its presence restored the pathological brain to a physiological state, contrasting the infiltration by Th17 cells [ 39 ]. KIR-SOCS1 effects in a type I diabetes mouse model revealed an atheroprotective role for this sequence because it caused improvements of renal functionality and fibrosis and the decrease of pro-inflammatory cytokines such as TNFα and INFγ or C-C motif chemokine ligand (CCL) 25 [ 52 , 53 ].…”
Section: Peptides and Peptidomimetics As Modulators Of Inflammatiomentioning
confidence: 99%
“…Previous studies revealed that SOCS1 and SOCS3 target JAK1 for degradation [23,24]. IAV infection upregulated SOCS1 and SOCS3, and SOCS1/3 antagonist peptide could protect mice against lethal in uenza infection [25,26]. Therefore, we investigated whether SOCS1 and SOCS3 are involved in the degradation of JAK1 during IAV infection.…”
Section: Iav Infection Induced Socs1 Mediate the Degradation Of Jak1mentioning
confidence: 97%